Governing childhood:|The juvenile justice system in Turkey - Sağlam, Didem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis aims to contribute to the critical approach to juvenile justice system by focusing on child imprisonment in Turkey. Even though juvenile justice system is a complex and rich topic that is able to make valuable contribution to children studies and the scholarship on prison and criminal justice system, the studies on this particular issue is largely insufficient. To do so, I conducted in-depth interviews between January 2017 and February 2018 in İstanbul, İzmir and Gaziantep with 10 male and 5 female respondents who were kept in prison when they were under the age of 18. On the basis of this research, I examine the historical development of child imprisonment and the transformation of juvenile justice system, as well as the relationship between the modern paradigm of childhood and children-related modern institutions. Specifically, I explore the dimension of time in child imprisonment by problematizing how the changing conceptualization of time affects punishment practices and the experience of ex-prisoners. I investigate the gender dimension of the juvenile justice system by taking issue with the “invisibility” of girls and by focusing on the masculine performances within prison. Lastly, my study examines the political economy of imprisonment, prison labour along with exchange and gift economy in prison. In doing so, my research shows the way juvenile justice system works through constructing juvenile delinquency and introduce punitive mechanisms in the name of “protecting” children.
Keywords: Juvenile justice, Administration of -- Turkey.; Children -- Government policy -- Turkey.